Examining the Factors Influencing Consumer Buying Behaviour of Instant Food among Residents in Kota Bharu Kelantan - Mat Zain, Nur Syafiqah (2020)
Food and culture eating of Malaysian residents have undergone some changes. Jebaraj in 2014 stated that consumers are showing much attention in new and good quality of instant food products. Instant food products are commercially prepared without additional preparation. Consumption of excessive instant food product has caused people eating huge amount of salt and sugar everyday which lead to several health problems. Marketers should be more concerned and have better understanding on consumer behaviour before they commercially produced the products. The main aim of this study was to identify the most significant factors that influence consumer buying behaviour of instant food among residents in Kota Bharu Kelantan. Questionnaire had been distributed to 384 respondents and using convenience sampling method. The reliability of questionnaire was checked using Cronbach's Alpha test. Result shown Cronbach's Alpha value was acceptable. Data had been analyzed using SPSS software. The descriptive statistical tests were used to analyze demographic profile of respondents. These 8 important factors accounted for 60.33% of total variance explained. Exploratory factor analysis revealed eight underlying factors regarding instant food which were 'marketing and branding attributes', 'appearance attribute and preferences', 'convenience', 'food safety', `products durability and availability', 'food hygiene and easiness', 'perceptions' and `lifestyle'. Understanding the factors that triggered consumer buying behaviour can help marketers to improve their sales that meet consumer demand. Thus, food producers are able to identify important attribute influencing consumer to buy instant food product and increase value of their product. This study can be served as an important insight regarding to the consumers need on instant food products.